Contesting Neoliberal Urbanism in Glasgow's Community Gardens: The Practice of DIY Citizenship†. Issue 4 (28th January 2016) - Crossan, John; Cumbers, Andrew; McMaster, Robert; Shaw, Deirdre
Abstract: In this journal, it has been suggested that citizens practising community gardening "can become complicit in the construction of neoliberal hegemony". Such hegemony is maintained, it is argued, through the day‐to‐day work of neoliberal citizen‐subjects, which "alleviates the state from service provision". In this paper we acknowledge that community gardens are vulnerable to neoliberal cooptation. But, even where neoliberal practices are evidenced, such practices do not define or foreclose other socio‐political subjectivities at work in the gardens. We contend that community gardens in Glasgow cultivate collective practices that offer us a glimpse of what a progressively transformative polity can achieve. Enabled by an interlocking process of community and spatial production, this form of citizen participation encourages us to reconsider our relationships with one another, our environment and what constitutes effective political practice. Inspired by a range of writings on citizenship formation we term this "Do‐It‐Yourself" (DIY) Citizenship.